2017
DOI: 10.1126/science.aap9580
|View full text |Cite
|
Sign up to set email alerts
|

SwiftandNuSTARobservations of GW170817: Detection of a blue kilonova

Abstract: With the first direct detection of merging black holes in 2015, the era of gravitational wave (GW) astrophysics began. A complete picture of compact object mergers, however, requires the detection of an electromagnetic (EM) counterpart. We report ultraviolet (UV) and X-ray observations by Swift and the Nuclear Spectroscopic Telescope ARray (NuSTAR) of the EM counterpart of the binary neutron star merger GW 170817. The bright, rapidly fading ultraviolet emission indicates a high mass (≈ 0.03 solar masses) wind-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
364
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 498 publications
(400 citation statements)
references
References 88 publications
25
364
1
2
Order By: Relevance
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 79%
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 79%
“…The individual light curves of the SGRB sample are shown in light blue. Already the Swift non-detections presented in Evans et al (2017b; downward pointing triangles in Figure 2) revealed that the afterglow is >1.5 dex fainter than the faintest SGRB with detected afterglow (downward pointing triangles in Figure 2). The deep Chandra observation by Troja et al (2017b) at 2.3days after GW170817 excluded any afterglow brighter than > -10 erg s 39 1 , i.e., a factor of 10 below the Swift upper limits.…”
Section: Grb 170817a In the Context Of Other Sgrbsmentioning
confidence: 99%
“…Fitting parameters for different lines are shown in Table 1 Table 2. Panel (a): The fitting of X-ray data (including black upper limits and red data-points) (Evans et al 2017;Troja et al 2017) with the two-component jet model. …”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Panel (a): The fitting of X-ray data (including black upper limits and red data-points) (Evans et al 2017;Troja et al 2017) with the structured jet model. Fitting parameters for different lines are shown in Table 1 Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation